What are the reasons why people take part in aerobic exercise at the gym? - Fransiska Noviana; Y. Touvan Juni Samodra; Uray Gustian (Sriwijaya Journal of Sport, 2023)
Maintaining fitness is a positive activity for life. There are many ways to maintain fitness. Aerobic exercise is one option to maintain fitness. The factor of laziness or busyness sometimes becomes an obstacle for people taking part in gymnastics, in addition to the long distance or the costs involved. This research aims to describe the motivation of aerobics exercise members to participate in exercise activities. Respondents consisted of gymnastics members in seven (7) gymnastics studios in Kuburaya, West Kalimantan, with a total sample of 86 people who filled out the questionnaire voluntarily. The research instrument is a questionnaire that asks for two variables: intrinsic and extrinsic motivation. The research data was analysed using descriptive statistics. The research results show that the intrinsic and extrinsic motivation values are almost the same, with a mean intrinsic value of 85.35 and extrinsic 81.45. Based on these results, it can be concluded that whatever the initial motivation and the process of remaining active in doing exercise, it will not be a problem. The most important thing is the continuity of aerobic activities to maintain fitness